ӘПСАНАЛАРДА ТРАНСФИГУРАЦИЯ ҚУБЫЛЫСЫ - Қалбаева, Г.С. (SCIENCE and SOCIETY, 2016)
In the article importance of poetic function of character appearance transformation motifs in the legend plot is proved and their role as the main element in an interpretation of character nature is analyzed.